2012
DOI: 10.1007/s00464-011-2142-y
|View full text |Cite
|
Sign up to set email alerts
|

Elective laparoscopic versus open colectomy for diverticulosis: an analysis of ACS-NSQIP database

Abstract: In the elective setting for symptomatic diverticulosis, LC seems to be associated with lower 30-day morbidity and complication rates compared with OC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 23 publications
0
12
0
1
Order By: Relevance
“…Multiple studies 24-27 have demonstrated that laparoscopic colon and rectal resections result in decreased complication rates as compared with open resection. In addition to decreased complications, patients who undergo laparoscopic colon and rectal resections have been shown to have shorter postoperative length of stay and improved overall and cancer free survival as compared with open resections, which may make the patients who have had open resections in the past better candidates for laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Multiple studies 24-27 have demonstrated that laparoscopic colon and rectal resections result in decreased complication rates as compared with open resection. In addition to decreased complications, patients who undergo laparoscopic colon and rectal resections have been shown to have shorter postoperative length of stay and improved overall and cancer free survival as compared with open resections, which may make the patients who have had open resections in the past better candidates for laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…25, 26, 30 However, interpreting results from these retrospective reviews is difficult as patients were offered laparoscopic versus open resection according to surgeon preference and historically laparoscopic surgery has been offered to earlier stage cancer patients at larger urban hospitals and younger patients with less comorbidities. 25-27 Therefore, it is difficult to ascertain if patients who undergo laparoscopic procedures have better outcomes due to the operative approach or because they were healthier with earlier stage disease preoperatively. Future studies comparing patients with similar comorbidities and cancer stage who receive laparoscopic versus open procedures as well as studies assessing why surgeons recommend laparoscopic versus open procedures would provide much needed clarification on this topic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For non-oncologic resections, similar results have been reported. Retrospective studies evaluating elective colectomy for diverticulosis and randomized trials such as the SIGMA have reported a significant reduction in postoperative morbidity with a minimally invasive approach[5,6]. Unfortunately, clinical trials in laparoscopic surgery have underrepresented the elderly and fail to account for frailty[7,8].…”
Section: Introductionmentioning
confidence: 99%